EVALUATION OF DRYING KINETICS OF SLURRED CERAMIC RAW MATERIALS - Agra, Ozden; Gonul, Alisan (TURKISH SOC THERMAL SCIENCES TECHNOLOGY, 2017)
One of the most popular applied methods during the production of ceramics is convective drying by mixing raw materials and a certain proportion of water to achieve homogeneity. In this study, drying characteristics of slurred raw materials have been evaluated according to different heat transfer mechanisms in a convective dryer. This experimental study was performed by using three different molds to understand the effects of heat and mass transfers from i) only one surface where the bottom surface was isolated, ii) two surfaces where one side of the mold was covered with an stainless steel plate to enhance heat transfer, iii) two surfaces. All experiments were conducted with two different thickness values for all three molds to determine the drying time of raw materials. The experimental results were compared to some thin-layer drying models from the literature. Midilli et. al. model was found the best relevant drying model. Also, effective moisture diffusion coefficients were found for different heat transfer mechanisms according to Crank's model (Crank, 1975).
Keywords: Convective drying; Slurred raw material; Heat transfer; Mass transfer; Effective moisture diffusion coefficient; MASS-TRANSFER; MODEL; FRUITS; DRYER; Thermodynamics; Engineering